2011
DOI: 10.4049/jimmunol.1003300
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Endotoxin Induces Inflammation by Selectively Removing Nuclear Receptors and Activating CCAAT/Enhancer-Binding Protein δ

Abstract: Subclinical levels of circulating endotoxin are associated with the pathogenesis of diverse human inflammatory diseases, by mildly inducing the expression of proinflammatory mediators. In this study, we examined the molecular mechanism responsible for the effect of low-dose LPS in macrophages. In contrast to high-dose LPS, which activates NF-κB and induces the robust expression of proinflammatory mediators, we observed that low-dose LPS failed to activate NF-κB. Instead, it selectively activated C/EBPδ and rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
74
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 32 publications
10
74
0
Order By: Relevance
“…95 The let-7c down-regulates C/EBP-d, an important transcriptional factor that is required for a sustained Toll-like receptor 4einduced inflammatory response, which promotes the M1 phenotype. 95,96 Similar to the role of let-7c, miR-124 diminishes M1 polarization and enhances M2 polarization in bone marrowederived macrophages from mice. Overexpression of miR-124 reduces expression of the surface markers CD45, CD11b, F4/80, major histocompatibility complex class II, and CD86, but increases the expression of the M2 phenotypic markers found in inflammatory zone 1 (FIZZ1) and arginine-1.…”
Section: Macrophage Plasticitymentioning
confidence: 99%
“…95 The let-7c down-regulates C/EBP-d, an important transcriptional factor that is required for a sustained Toll-like receptor 4einduced inflammatory response, which promotes the M1 phenotype. 95,96 Similar to the role of let-7c, miR-124 diminishes M1 polarization and enhances M2 polarization in bone marrowederived macrophages from mice. Overexpression of miR-124 reduces expression of the surface markers CD45, CD11b, F4/80, major histocompatibility complex class II, and CD86, but increases the expression of the M2 phenotypic markers found in inflammatory zone 1 (FIZZ1) and arginine-1.…”
Section: Macrophage Plasticitymentioning
confidence: 99%
“…Recent studies from our group and other suggest another intriguing aspect of innate immunity programming and memory, in that innate leukocytes may not only be able to recognize different combinations of extra-cellular stimulants, but also discern their relative signal strength (Baker et al, 2014;Deng et al, 2013;Lu et al, 2015;Maitra et al, 2012;Maitra et al, 2011;Morris et al, 2014). This is reflected in the cardinal example of endotoxin priming and tolerance.…”
Section: Signal Strength-dependent Programming Of Innate Leukocytesmentioning
confidence: 93%
“…For example, we and others demonstrated that nuclear receptors (e.g. RAR, ROR) activated by retinoic acid can not only synergize with signal transducer and activator of transcription 4 (STAT4) activated by IL-4, but also can potently suppress the inflammatory NFB pathway activated by LPS Maitra et al, 2011).…”
Section: Combinatorial Programming With Multiple Immune Stimulantsmentioning
confidence: 99%
“…From these data, it is clear that the same probiotic strain at different doses can exert qualitatively different modulating effects on DCs and consequently on adaptive immune responses induced by rotavirus vaccines. It has been reported that the effect of low dose microbe-associated pattern molecular (MAPM), such as lipopolysaccharide, was strikingly different as compared to that of high dose on macrophage cell functions: low dose lipopolysaccharide induced a strong inflammatory response in macrophages (Maitra et al, 2011). It is plausible that a similar interaction occurs between the MAPM from LA and DCs in the gut.…”
Section: Dose Effects Of La On DC Responsesmentioning
confidence: 93%